The Utility of Peripheral Blood Leucocyte Ratios as Biomarkers in Neonatal Sepsis: A Systematic Review and Meta-Analysis - Zhang, Juanjuan; Zeng, Jun’an; Zhang, Liangjuan; Yu, Xiping; Guo, Jinzhen; Li, Zhankui (Frontiers in Pediatrics, 2022)
Background: Early diagnosis of sepsis in neonates is hampered by non-specific symptoms and a lack of rapid-response laboratory measures. The full blood count is a cheap, fast, and ubiquitous laboratory test that can be used for diagnoses. Method: The aim of the present study was to assess the diagnostic accuracy of immature to total neutrophil ratio (ITR), immature to mature neutrophil ratio (IMR), neutrophil to lymphocyte ratio (NLR), and platelet to lymphocyte ratio (PLR) in the diagnosis of neonatal sepsis. We searched four databases and relevant references to identify studies that met the inclusion criteria. Pooled sensitivities and specificities were calculated, I² was used to test for heterogeneity, and the source of heterogeneity was investigated via meta-regression analysis. Results: A total of 38 studies met the inclusion criteria. A total of 31 studies (6,221 neonates) included data on the ITR, 8 studies (1,230 neonates) included data on the IMR, 7 studies (751 neonates) included data on the NLR, and 2 studies (283 neonates) included data on the PLR (some studies had data on more than one test). The summary sensitivity estimates (95% confidence interval (CI)) for the ITR, IMR, NLR, and PLR tests were 0.74 (95% CI 0.66–0.80), 0.74 (95% CI 0.54–0.88), 0.73 (95% CI 0.68–0.78) and 0.81 (95% CI 0.55–1.00), respectively. The summary specificity values for the ITR, IMR, NLR, and PLR tests were 0.83 (95% CI 0.77–0.87), 0.89 (95% CI 0.80–0.94), 0.69 (95% CI 0.57–0.79), and 0.93 (95% CI 0.81–1.00), respectively. The summary receiver operating characteristic curves for the ITR, IMR, and NLR tests were 0.85 (95% CI 0.82–0.88), 0.91 (95% CI 0.88–0.93), and 0.75 (95% CI 0.71–0.79). The PLR could not be evaluated because only two studies included pertinent data. Conclusions: The NLR test does not appear to be sufficiently accurate to be helpful in the diagnosis of neonatal sepsis. The ITR and IMR tests alone can improve the accuracy of neonatal sepsis diagnosis, but the marked heterogeneity and the limited number of studies prevented reaching definitive conclusions. Thus, further studies are required to confirm these findings.